1996
DOI: 10.1002/(sici)1096-9896(199610)180:2<138::aid-path652>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Ret Proto-Oncogene in Sporadic Parathyroid Adenomas

Abstract: Missense germline mutations of the RET proto‐oncogene have recently been identified in the hereditary cancer syndromes MEN2A, MEN2B, and FMTC, all characterized by medullary carcinoma, but also including phaeochromocytoma in MEN2A and MEN2B and parathyroid disease in MEN2A. In addition, somatic RET proto‐oncogene mutations have been identified in a subset of sporadic medullary carcinomas and phaeochromocytomas. This study investigated the possibility that RET plays a role in sporadic parathyroid neoplasia. Fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Our results indicate that RET mutations in exons 10, 11, and 13–16 do not account for the formation of PGLs, as opposed to MTCs and PCCs, and that there is no common genetic defect in PGLs and PCCs, despite their common embryological origin and histological similarities. Similarly, in sporadic parathyroid adenomas, no exon 10 or 11 RET mutations were detected, although RET expression was shown by RT‐PCR20. However, because not all parts of the RET proto‐oncogene have been examined and we did not test for RET translocations, we cannot entirely exclude a possible role for RET in the formation of PGLs.…”
Section: Discussionmentioning
confidence: 93%
“…Our results indicate that RET mutations in exons 10, 11, and 13–16 do not account for the formation of PGLs, as opposed to MTCs and PCCs, and that there is no common genetic defect in PGLs and PCCs, despite their common embryological origin and histological similarities. Similarly, in sporadic parathyroid adenomas, no exon 10 or 11 RET mutations were detected, although RET expression was shown by RT‐PCR20. However, because not all parts of the RET proto‐oncogene have been examined and we did not test for RET translocations, we cannot entirely exclude a possible role for RET in the formation of PGLs.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, the activation of RET by other mechanisms or rearrangements that are currently not yet identified might also be involved in the carcinogenesis of PTCs. These might explain the slightly higher proportion of PTCs with RET activation identified by Williams et al using an RT-PCR approach to identify RET mRNA expression compared with results obtained from studies identifying specific types of RET rearrangements with Southern blotting or RT-PCR [104].…”
Section: Ret In Papillary Thyroid Carcinomamentioning
confidence: 89%
“…These include Southern blotting, requiring high-quality DNA extracted from unfixed tumour and nontumour tissues [31] and reverse transcription (RT)-PCR-based techniques to identify both specific RET rearrangements [95] and gene activation [104]. The latter methods are also suitable for the analysis of archival materials, and Williams et al have demonstrated that the use of a nested RT-PCR approach for the analysis of RET tyrosine kinase expression can significantly improve the sensitivity of their assay [104]. A third method of analysing RET overexpression in PTCs is the immunohistochemical detection of the RET gene product in tissue sections [100].…”
Section: Ret In Papillary Thyroid Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…A tissuespecific threshold effect may exist whereby C cells and adrenal cells are most and parathyroid cells are least vulnerable to the growth-promoting effects conferred by the RET oncogene (12,48,49). The fact that phenotypic differences between MEN-2A and FMTC exist although individuals with these disorders may have identical RET mutations, suggests that other genetic and/or environmental factors may modulate the development of phenotypes in MEN-2.…”
Section: Genotype-phenotype Correlationmentioning
confidence: 99%